2020
DOI: 10.1002/lary.29212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Surgery on C‐Reactive Protein Levels in Adults With Obstructive Sleep Apnea: A Meta‐Analysis

Abstract: Objectives/Hypothesis To evaluate associations between sleep surgery and CRP (C‐reactive protein) levels in adults with obstructive sleep apnea (OSA). Study Design Meta‐analysis. Methods Two authors independently searched PubMed, Medline, EMBASE, and Cochrane review databases until July 2019. The keywords used were sleep apnea, OSA, sleep apnea syndromes, surgery, C‐reactive protein (CRP), and inflammatory markers. The effects of sleep surgery on CRP levels were examined using a random‐effects model. Results N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
7
2
Order By: Relevance
“…In this meta‐analysis, we were unable to clarify the factors associated with cytokine changes after sleep surgery. Our previous meta‐analysis identified that OSA improvement was associated with C‐reactive protein changes after sleep surgery 25 . By contrast, according to our analysis, OSA improvement was not significantly associated with cytokine changes.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In this meta‐analysis, we were unable to clarify the factors associated with cytokine changes after sleep surgery. Our previous meta‐analysis identified that OSA improvement was associated with C‐reactive protein changes after sleep surgery 25 . By contrast, according to our analysis, OSA improvement was not significantly associated with cytokine changes.…”
Section: Discussioncontrasting
confidence: 64%
“…Several surgical procedures, including nasal surgery, 52,53 uvulopalatopharyngoplasty, 54 multilevel surgery, 55,56 maxillomandibular advancement, 57,58 tracheostomy, 59 and hypoglossal nerve stimulation, 60,61 have been introduced based on patients' anatomy, and they have different surgical outcomes. Our recent meta‐analysis in 2021 revealed that sleep surgery for OSA resulted in a significant reduction of C‐reactive protein levels in adults 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the procedure, an average of 0.25mg / L was measured, and 30 days after surgery, 0.12mg / L, a decrease of 0.13mg / mL. Usually in human beings with obstructive sleep syndrome, there are increased values of C-reactive protein, with a significant reduction in the levels of this biomarker in adult patients after surgical treatment (Kang et al, 2020). Although brachycephalic dogs do not develop an inflammatory condition as expressive chronic as humans with anterior airway obstruction, rhinoplasty with diode laser was able to decrease C-reactive protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that in human patients with obstructive sleep syndrome, age is a risk factor for the disease, since it is diagnosed regularly in adult patients (Kang et al, 2020). In brachycephalic dogs, the severity of the condition is directly linked to the obstructive components, and clinical manifestation is also common in very young animals due to the intense selection to which they were submitted.…”
Section: Discussionmentioning
confidence: 99%